2013
DOI: 10.1158/1078-0432.ccr-12-3919
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Activity and Safety of Combination Therapy with Temsirolimus and Bevacizumab for Advanced Melanoma: A Phase II Trial (CTEP 7190/Mel47)

Abstract: Purpose A CTEP-sponsored phase II trial was performed to evaluate safety and clinical activity of combination therapy with CCI-779 (temsirolimus) and bevacizumab in patients with advanced melanoma. Experimental Design Patients with unresectable stage III to IV melanoma were treated intravenously with temsirolimus 25mg weekly and bevacizumab 10mg every 2 weeks. Adverse events were recorded using CTCAE v3.0. Tumor response was assessed by Response Evaluation Criteria in Solid Tumors, and overall survival was r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…Our choice of models was based on rapalogs indications in renal and breast carcinoma (4,5,7) and their current evaluation in melanoma (41). In contrast with that in RENCA and 4T1 tumors, we observed that T-cell subsets can differentially shape the efficacy of rapalogs against B16-OVA tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Our choice of models was based on rapalogs indications in renal and breast carcinoma (4,5,7) and their current evaluation in melanoma (41). In contrast with that in RENCA and 4T1 tumors, we observed that T-cell subsets can differentially shape the efficacy of rapalogs against B16-OVA tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…With a prevalence of approximately 2.8% of the US population (1.4% axillary and 0.5% palmar, by national survey),3 HH is an often overlooked disorder that has significant impact on psychosocial functioning of affected patients 46. A family history is often reported by patients affected by HH, supporting a basis of genetic transmission that has been explored by Ro et al7 in a recent study 2.…”
Section: Introductionmentioning
confidence: 88%
“…The diagnosis of primary HH, which is, by definition, not associated with an underlying condition, requires that other (potentially more serious) causative pathologies be ruled out 4. Secondary HH, in contrast, may be attributed to a number of other conditions, including endocrine disturbances, drugs, certain malignancies, and central nervous system abnormalities 4. HH can be further distinguished by anatomic distribution of affected regions and by laterality: unilateral versus bilateral and symmetrical 4.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the Cancer Therapy Evaluation Program trial led by Slingluff et al showed that temsirolimus and bevacizumab elicited an objective clinical response in patients with BRAF/RAS−wild-type melanomas. These results suggest that the combination of an angiogenesis inhibitor with an mTOR pathway inhibitor (25 mg temsirolimus weekly and 10 mg bevacizumab every 2 weeks) is a promising a regimen for a subset of melanoma patients who lack activating mutations in both BRAF and RAS and for whom no targeted therapies are currently available 86. However, no study has shown that bevacizumab as monotherapy offers a significant survival benefit over conventional therapies.…”
Section: The Current State Of Antiangiogenic Therapies In Melanomamentioning
confidence: 99%